2022
DOI: 10.1136/bmjopen-2021-055501
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of lower extremity disease in high risk groups in Malawi: a stratified cross-sectional study

Abstract: ObjectiveLow/middle-income countries face a disproportionate burden of cardiovascular diseases. However, among cardiovascular diseases, burden of and associations with lower extremity disease (LED) (peripheral arterial disease and/or neuropathy) is neglected. We investigated the prevalence and factors associated with LED among individuals known to have cardiovascular disease risk factors (CVDRFs) in Malawi, a low-income country with a significant prevalence of CVDRFs.DesignThis was a stratified cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Finally, associations have been observed between long-term exposure to air pollutants, including carbon monoxide and particulate matter, and PAD 42 . While outdoor air pollution is not substantial in Agincourt, HAALSI participants may have been exposed to high levels of indoor air pollutants from indoor cooking with fire as observed in similar settings elsewhere 28 . These risk factors warrant future exploration in the HAALSI cohort.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, associations have been observed between long-term exposure to air pollutants, including carbon monoxide and particulate matter, and PAD 42 . While outdoor air pollution is not substantial in Agincourt, HAALSI participants may have been exposed to high levels of indoor air pollutants from indoor cooking with fire as observed in similar settings elsewhere 28 . These risk factors warrant future exploration in the HAALSI cohort.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, our prevalence measures were higher than prior estimates from LMIC settings performed in similar age groups. Studies from the Philippines, Malawi, and China estimated a prevalence of PAD ranging from 2% to 5% for comparable age groups [28][29][30][31] . Similarly, a previous global analysis concluded that LMICs have higher PAD prevalence at younger ages compared to high-income countries 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Philippines, Malawi, and China estimated a prevalence of PAD ranging from 2% to 5% for comparable age groups. 27 , 28 , 29 , 30 Similarly, a previous global analysis concluded that LMICs have higher PAD prevalence at younger ages compared with high‐income countries. 8 We estimated the prevalence of clinical PAD in HAALSI participants aged 40 to 49 years as well as aged 50 to 59 years to be over 2 times higher than estimates from the United States.…”
Section: Discussionmentioning
confidence: 92%
“… 43 While the linkage between indoor air pollution and PAD is limited, prior research in Malawi found an association between indoor fire exposure and lower extremity disease while other work in sub‐Saharan Africa has found an increased risk of cardiovascular disease associated with indoor biomass cooking. 27 , 44 , 45 , 46 These risk factors warrant future exploration in the HAALSI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The LMICs are particularly vulnerable to the devastating effects of LEAD given the lack of awareness, limited availability of diagnostic tools and poor health care infrastructure. The prevalence of LEAD and its complications are expected to rise exponentially in these parts of the world with attended significant impact on overall morbidity and mortality 1 , 2 , 6 , 7 , 14 .…”
Section: Discussionmentioning
confidence: 99%